Lifetime History of Concussion Among Youth With ADHD Presenting to a Specialty Concussion Clinic - Cook, Nathan E.; Teel, Elizabeth; Iverson, Grant L.; Friedman, Debbie; Grilli, Lisa; Gagnon, Isabelle (Frontiers in Neurology, 2022)
Child and adolescent student athletes with attention-deficit/hyperactivity disorder (ADHD) report a greater lifetime history of concussion than those without ADHD. This case-control study compared youth with and without ADHD presenting for care at a specialty concussion clinic on their lifetime history of concussion. We hypothesized that a greater proportion of youth with ADHD would report a history of prior concussion. Archival clinical data from patients presenting to a specialty concussion clinic in Montreal, Québec, Canada between September 2015 and August 2019 were analyzed. The sample included 2,418 children and adolescents (age: M = 13.6, SD = 2.7, range 5–18 years; 50.9% girls), including 294 (12.2%) with ADHD and 2,124 (87.8%) without ADHD. The proportion with prior concussion among youth with ADHD (43.9%) was significantly greater than youth without ADHD [37.5%, χ2 = 4.41, p = 0.04, OR = 1.30, 95% confidence interval (CI): 1.02–1.67]. A significantly higher proportion of boys with ADHD had a prior concussion history (48.1%) than boys without ADHD [38.4%, χ2 = 5.33, p = 0.02, OR = 1.48 (95% CI: 1.06–2.09)], but this difference was not observed for girls (χ2 = 0.31, p = 0.58). Youth with ADHD did not differ with regard to their estimated longest duration of symptoms from a prior concussion (Z = 1.52, p = 0.13) and the proportion who reported taking longer than 28 days to recover from a prior concussion did not differ between those with ADHD (15.3%) and without ADHD (12.2%), χ2 = 2.20, p = 0.14. Among youth presenting to a specialty clinic, ADHD was associated with greater lifetime history of concussion but not a greater duration of symptoms from a prior injury.